3-D views of the expanding CME: from the Sun to 1AU. (5th March 2015) - Rouillard, Alexis P.
Abstract: Three-dimensional information on Coronal Mass Ejections (CMEs) can be obtained from a wide range of in-situ measurements and remote-sensing techniques. Extreme ultraviolet (EUV) and white-light imaging sensed from several vantage points can be used to infer the 3-D geometry of the different parts that constitute a CME. High-resolution and high-cadence coronal imaging provides detailed information on the formation and release phase of a magnetic flux rope, the lateral expansion of the CME and the reconfiguration of the corona associated with the effects of pressure variations and reconnection. The evolution of the CME in the interplanetary medium and the connection of its various substructures with in-situ measurements can be obtained from multi-point heliospheric imaging.